Levitikus as agtergrond van Markus 5:25–34, geïnterpreteer in terme van eer-en-skaamte - Roux, Elritia le (HTS teologiese studies, 2011)
This article investigated whether Mark 5:25–34 proposes a radical discontinuity with the Jewish purity codes and subsequently, holds drastic liberating implications for women as far as access to the temple is concerned and more existentially speaking, access to Yahweh. It determined whether Leviticus speaks about women in such an androcentric and exclusive manner and whether Jewish culture is indeed so discriminating. This article argued that Mark 5:25–34 does indeed radically turn the Jewish purity codes upside down and that the Jesus movement proclaims a drastic liberation for women from social marginalisation. However, the original meaning of the text in Leviticus should not be viewed so negatively. The dreadful consequences of the exile and the destruction of the temple lead to the idea amongst the orthodox rabbi’s that the purity codes should be maintained in a very strict way. These codes were thought to ensure that the holiness of Yahweh would manifest in the social sphere, the people of Yahweh would be blessed and a catastrophe of these immense proportions would be avoided in future. Unfortunately, this lead to the degeneration of the cult, that became exclusive as many people were deprived from the presence of Yahweh. The author of the Gospel according to Mark is reacting to this and clearly voices his criticism against this marginalisation.